Linkage Between External and Internal Imbalance – The Case of Serbia - Živkov, Dejan; Njegić, Jovan; Ljumović, Isidora Lj (Industrija, 2013)
After a while almost all transition and emerging countries that have entered into the process of economic reforms became attractive for foreign direct investments and foreign loans. Consequently, huge amount of capital inflow lead to the surpluses in the financial-capital account. Capital that has entered the system usually converts into the local currency and thus contributes to the growth of money supply in the system. However, high level of money supply leads to internal imbalances such as relatively high inflation and unstable exchange rate. In this paper we will try to give an answer to whether above described scenario is characteristic for Serbian transition economy. In this process we will use linear regression, vector auto-regression (VAR) and error correction model.
Keywords: External and internal imbalance; Transmission channel; Vector auto-regression; Error correction model